Knowledge and Perception of Brazilian Dental Students about Molar-Incisor Hypomineralization - Thalys Gustavo Oliveira Martins; Naiara Oliveira Carvalho; Cristiane Tomaz Rocha; Beatriz Gonçalves Neves (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the knowledge and perception of Brazilian dental students regarding molar incisor hypomineralization (MIH). Material and Methods: A cross-sectional study was conducted with dental students from a dental school in the Northeast region. A self-administered questionnaire was applied, containing questions about MIH, including etiology, diagnosis, and treatment. Clinical photographs assessed students’ ability to differentiate MIH from other enamel defects. Chi-square or Fisher’s exact test was used for associations, and the Kruskal-Wallis test for comparisons, considering the academic year as the independent variable. Results: 67 students participated, primarily enrolled in the third and fifth years. The majority (68.7%) reported familiarity with MIH, and 82.1% recognized it as a qualitative defect. MIH awareness was significantly associated with fifth-year students (p=0.01). Genetic factors were considered as an etiological factor by 80.6%. None of the students felt "very confident" in diagnosing MIH. No difference was observed in confidence levels across academic years. Enamel hypoplasia (64.2%) was cited as the most challenging differentiating condition from MIH. Students demonstrated uncertainty in diagnosing severe MIH (20.9%), whereas fluorosis was the defect most easily recognized (71.6%). Conclusion: Dental students demonstrate knowledge of MIH and recognize some clinical characteristics but lack confidence in diagnosing it. This highlights the need for enhanced dissemination and teaching of MIH in undergraduate dental education.